PHARMACOLOGICALLY ACTIVE FATTY ACIDS OF FIDDLER CRAB Uca acuta acuta (Simpson) : Life Science-Zoology - TAPAS KUMAR DAS; GHOSH, ANITA; KUMAR CHAKRABORTY, SUSANTA (International Journal of Life Science and Pharma Research, 2014)
The fatty acid compositions of the body flesh, big chela flesh and hepatopancreas of the selected detritivore fiddler crab Uca acuta acuta (Simpson) have been studied by gas liquid chromatography and other chromatographic techniques. Altogether 28 components were detected and estimated. Major fatty acids recorded were palmitic (16:0), stearic (18:0), oleic (18:1ω9), linoleic (18:2ω6), arachidonic (20:4ω3), eicosapentaenoic (20:5ω3) and docosahexaenoic (22:6ω3). Of the polyunsaturated fatty acids, considerably higherlevels of pharmacologically active fatty acids, viz. eicosapentaenoic and Docosahexaenoic acids were recorded. Such findings suggests that the species studied is also a potential source of pharmacologically active fatty acids, particularly those belonging to the –ω3 series.